ON STOCHASTIC ESTIMATION OF THE RESULTS OF UNDULATORY TRANSILLUMINATION OF SOLID MATERIALS WITH A PAUCITY OF MEASUREMENTS - S. N. Osipov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The methods of undulatory transillumination found extensive application in engineering and mining practice. They are based on utilization of the parameters of reflected and transmitted waves produced by way of affecting solid materials and formations with diverse sources. In recent years a simplistic technique of the productive-process robust designing enjoys widespread occurrence. It uses notions of ‘signal’ and ‘noise’ and a tenth part of the logarithm value of the reciprocal magnitude of the dispersion squared value corresponds the ratio of the signal and the noise. The article utilizes the confidence boundaries evaluation techniques for dispersion in robust design on chi-square criterion at small sample specified by K. A. Brownly under editorial of academician А. N. Kholmogorov, which essentially increases reliability of the stochastic estimations.Exemplarily of quantitative assessment in the reliability determination of anomalous zones in mining conditions, the author shows the tracing of a map of the formation graph of regular components of the elastic wave field at seismal transillumination along the layerage of the soliferous rocks of lower industrial pad III of potash horizon of the Starobinski minefield. The article claims the feasibility of the offered technique for stochastic estimation of the measurement results of any process where it is necessary to evaluate the reliability of the signal extraction against the noise background. A simple conditional scale built on basis of time and noise level values taken as a unit is convenient to use. The presented alignment chart and graphical dependencies allow quickly appraise the realization probability of the signalto-noise relation and possibility of its rise. Thereat the obtained evaluations depend little on the probable magnitudes distribution form of the employed value.